Adaptation improves discrimination of face identity - Oruç, Ipek (The Royal Society, 2011)
Whether face adaptation confers any advantages to perceptual processing remains an open question. We investigated whether face adaptation can enhance the ability to make fine discriminations in the vicinity of the adapted face. We compared face discrimination thresholds in three adapting conditions: (i) same-face: where adapting and test faces were the same, (ii) different-face: where adapting and test faces differed, and (iii) baseline: where the adapting stimulus was a blank. Discrimination thresholds for morphed identity changes involving the adapted face (same-face) improved compared with those from both the baseline (no-adaptation) and different-face conditions. Since adapting to a face did not alter discrimination performance for other faces, this effect is selective for the facial identity that is adapted. These results indicate a form of gain control to heighten perceptual sensitivity in the vicinity of a currently viewed face, analogous to forms of adaptive gain control at lower levels of the visual system.